Variation of LSP Collocations in the German and Austrian Civil Code - Księżyk, Felicja (Papers in Linguistics, 2020)
As we know, German is a pluricentric language with national variants/centers, which in relation to the language of law also differs due to the different legal systems in various German-speaking countries. Austrian civil code (ABGB), in force since 1811, is almost an entire century older than its counterpart in the Federal Republic of Germany (BGB), which came into force in 1900. This time gap also entails differences in the language of the two codes. The aim of the article is to show common features as well as differences within the collocation in German and Austrian civil code, which until now, were almost entirely left outside the research area.